The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/cb.2129
|View full text |Cite
|
Sign up to set email alerts
|

Nudging green food: The effects of a hedonic cue, menu position, a warm‐glow cue, and a descriptive norm

Abstract: Meat consumption is associated with both public health risks and substantial CO 2 emissions. In a large-scale field-experiment, we applied four nudges to the digital menus in 136 hamburger restaurants. The nudges promoted vegetarian food purchases by either (1) changing the menu position of vegetarian food, or aligning vegetarian food with (2) a hedonic, taste-focused nudge, (3) the warm-glow effect, or (4) a descriptive social norm. These nudges were thus aimed to shift salience toward a certain goal or the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Specifically, descriptive dynamic messages may hold more promise for reducing meat intake for three main reasons. First, the messages explicitly specify the behaviour required (reducing meat intake), contrasting previous usage of descriptive messages to influence meat consumption (e.g., Alblas et al, 2022;Reinholdsson et al, 2022). Second, the social norm message aligns with previous studies that supported the effects of descriptive messages to increase healthy food choices (e.g., Payne et al, 2015;Thomas et al, 2017).…”
Section: Open Access Edited Bymentioning
confidence: 58%
See 2 more Smart Citations
“…Specifically, descriptive dynamic messages may hold more promise for reducing meat intake for three main reasons. First, the messages explicitly specify the behaviour required (reducing meat intake), contrasting previous usage of descriptive messages to influence meat consumption (e.g., Alblas et al, 2022;Reinholdsson et al, 2022). Second, the social norm message aligns with previous studies that supported the effects of descriptive messages to increase healthy food choices (e.g., Payne et al, 2015;Thomas et al, 2017).…”
Section: Open Access Edited Bymentioning
confidence: 58%
“…Findings showed that regardless of condition (e.g., descriptive social norm or control), high meat consumers reduced meat intake, while low meat consumers increased meat intake over two weeks. While this study was limited by self-report dietary measures which are prone to inaccuracies (Heitmann and Lissner, 1995), a further study in Swedish fast-food outlets which displayed a descriptive social norm message and measured the number of 'green' or vegetarian sales, also reported no effects on intake (Reinholdsson et al, 2022). However, a key limitation in both these studies was that the descriptive social norm message presented did not explicitly refer to reduced meat intake.…”
Section: Open Access Edited Bymentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, a large-scale field study evaluated the effect of four different nudging strategies (i.e., normative goal, hedonic goal, a combination of normative and hedonic influence, and menu placement) to promote the purchase of green foods category (i.e., vegetarian and vegan options) in fast-food restaurants. Placement of the green category at the top of the menu led to a significant increase in the number of vegetarian and vegan dishes chosen [ 47 ]. As confirmation of this, among the implicit techniques applicable to the food choice environment, menu re-ordering was found to be the most effective in guiding diners’ decision making towards low-environmental impact dietary selections [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that the taste message was most effective, leading to a significant 10 percent increase in plant-rich food sales compared to when no message was present. If scaled across all MAX Burger outlets, researchers estimated that this minor change to wording would translate to around 140,000 extra sales of green menu options over the course of a year (Reinholdsson et al 2023). Since this time, MAX Burger has continued to expand its range of tasty plant-rich options and ensure that these are framed as positive choices in its "Supreme Green" menu.…”
Section: Case Studymentioning
confidence: 99%